Isolation and characterization of pigmented bacteria for dye sensitized solar cell application - Yonas, Mehari Tesfamariam (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Presently, the burning of fuel for electricity production contributes greatly to global warming and hence the need for clean, renewable source of electricity has never been greater. Dye sensitized solar cells (DSSCs) are amongst the newest and promising technologies that have great potential to be an alternative for the development of a new generation of photovoltaic devices. Bacterial pigments due to their biodegradability and higher compatibility with the environment offer promising avenues for various applications such as electricity production. In this project, natural bacterial pigments were applied as sensitizers in the DSSCs and their performances were studied. Pigment producing bacteria species such as Serratia maercescens, Chromobacterium violaceum and Bacillus cibi were isolated and their pigments extracted and characterized prior to their application in the DSSCs.